The impact of process parameters on the responses of a diesel engine running on biodiesel-diesel blend: An optimization study - Sarah Oluwabunmi Bitire; Tien-Chien Jen (Egyptian Journal of Petroleum)
The study sought to investigate the combined impact of parsley biodiesel blend (PSB) proportion, engine speed, and load on diesel engine parameters. The obtained result revealed that an increase in the proportion of PSB blend as the load increases, led to a rise in brake thermal efficiency (BTE), oxides of nitrogen (NOx), and a decline in brake specific fuel consumption (BSFC), carbon monoxide (CO) and brake specific energy consumption (BSEC) but no interactive effect of both factors hydrocarbon (HC). Also, varying the engine speed and proportion of PSB blend declined BSFC, BSEC, HC, and NOx bur raised BTE and CO. A blend of 20.22%, engine speed of 1483.39 rpm, and engine load of 95.88% were the best variables for the tested engine to achieve better performance and reduced emission utilizing the desirability-based method. The projected values for BTE, BSFC, BSEC, CO, HC, and NOx responses were 20.61%, 0.32 kg/kWh, 6.14 MJ/kW, 0.08963%, 18.28 ppm, and 347.72 ppm respectively. Furthermore, for the tested engine, the engine speed was determined to be the most significant variable (with the most influence) when compared to the engine load and fuel blend. This study is beneficial to researchers and organizations working on improving engine performance and reduction of toxic emissions to the environment. The optimization study can also help overcome the high cost and lengthy experimental techniques.